Spreading of Corona Virus in Central Europe: The Cases of Italy and Spain and the Very Beginning of Pandemic - Nieto-Chaupis, Huber (2022)
In this paper a mathematical model that focuses at the very beginning of pandemic at Europe is presented. In essence it is assumed that once the virus arrived to Italy then the geographical propagation was done through probabilistic rules among then to Spain. Because of this the model of propagation of Feynman in conjunction to Wiener schemes have been used to model the displacement of virus from Wuhan to Milan as well from Milan to Spain, as seen at the end of 2019 triggering the beginning of European pandemic at January of 2020. As seen at official data Italy and Spain have presented same statistics at the first months of local pandemic. From the usage of the proposed formalism, it is found that the country data are following Gaussian-like distributions due to the space-time propagation of virus.